Minimally-invasive anterior maxillary distraction technique in patients with cleft lip and palate and maxillary deficiency: an evaluation of 106 patients. Issue 7 (September 2020) - Shetty, V.; P, N.K.; Khanum, A.; Yadav, A.; Sailer, H.F.
Abstract: Our aim was to evaluate the feasibility of a minimally-invasive surgical technique for anterior maxillary distraction osteogenesis to correct maxillary hypoplasia in patients with clefts. A modified Y distractor was placed intraorally in 106 patients with cleft- associated maxillary deficiency to facilitate protraction of the maxilla. Subsequently the patients had an anterior maxillary osteotomy through a minimally invasive incision, followed by activation of the appliance at the rate of 0.8 mm/day until positive overjet was achieved. The patient's lateral cephalograms were evaluated preoperatively (T1), after activation (T2), and one year postoperatively (T3). Collected data were assessed with the paired t test, and probabilities of < 0.001 were accepted as significant. A mean (SD) of 10.4 (2.58) mm anterior maxillary advancement was obtained in all patients after 10-13 days of distraction. The sella–nasion-point A (SNA) angle increased from 75.37° to 83.01°. When we compared the cephalometric variables at T1 and T2, the mean maxillary length and overjet at T2 were significantly higher (p < 0.001). The comparison of mean values at T2 and T3 was not significant. Minimally invasive anterior maxillary distraction with the modified Y distractor resulted in changes after activation that were consistent one year postoperatively, making it a conservative, less traumatic, and effective treatment of cleft-related maxillary deficiency.